Swimming velocity improved by specific resistance training in age-group swimmers - Mavridis, G.; Kabitsis, C.; Gourgoulis, V.; Toubekis, A. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of the study was to examine the influence of a 12-week sprint-resisted training period on 10m sprint swimming time (T 10) and competitive performance (P). Eighty-two (n = 82) swimmers were assigned to an experimental (E, n = 53) and control (C, n=29) group and followed three sprint training sessions per week, with and without resistance respectively. Resistance was applied by a bowl tethered with an elastic rope to the hip of the swimmer. Post-training T10 was improved compared to pre-training (p<0.05). Group E displayed significant T10 improvement compared to group C (8.5±4.1% vs. 1.2±1.6%, p<0.05). Percent improvement of P on distances of 50-100-200m was higher in group E compared to C (p<0.05). The applied form of sprint-resisted training method is recommended for development of speed and may also be effective for competitive improvement.